Analysis of Digital Education Communication Strategies in Strengthening Youth Digital Literacy Toward Excellent Human Resources in 2045 - Leni Rohida; Nursahidin (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2026)
Digital transformation in education requires adaptive and strategic communication approaches to ensure that the learning process contributes effectively to the development of superior human resources (HR) toward the vision of Indonesia Emas 2045. This study aims to analyze digital education communication strategies in strengthening youth digital literacy as an integral component of HR development in the digital era. The research was conducted through a literature study and conceptual review of recent scientific sources that discuss communication, digital education models, and digital literacy frameworks. The findings indicate that the effectiveness of communication in digital-based education systems is strongly influenced by multi-stakeholder collaboration, involving schools, families, the government, digital platforms, and the private sector. In addition, the integration of interactive media, technology-supported learning methods, and active youth involvement in digital learning environments enhances knowledge absorption and critical engagement. The study argues that participatory, collaborative, and value-oriented communication strategies are essential for forming young generations who are critical, creative, technologically proficient, and possess strong digital ethics and citizenship. Strengthened digital literacy not only contributes to academic achievement but also develops future competencies such as problem solving, innovation, and global communication, which are crucial for future national competitiveness. The recommendations highlight the necessity of sustainable digital literacy initiatives, continuous capacity building for educators, and the creation of inclusive digital learning ecosystems. These efforts are positioned as key foundations for preparing competitive superior human resources who are adaptive, globally oriented, and able to contribute significantly to Indonesia’s socio-economic transformation in the global era and future